HIV Care in Asian and Pacific Islanders in Kansas. (8th January 2019) - Pichetsurnthorn, Pie; Pankow, Stephanie; Sweet, Donna; Kallail, Ken James
A complex cultural dynamic within the Asian and Pacific Islander (APIs) population contributes to barriers in HIV care. This qualitative narrative study investigated how awareness, resource accessibility, and cultural taboo impact HIV care in APIs in Kansas. Eleven HIV-infected API patients were interviewed. Two evaluators independently completed a qualitative themes analysis. Important themes impacting HIV care included lack of awareness, sex as a taboo topic, and misconceptions about HIV infection. These factors create a closed community regarding HIV prevention and care. Clinicians must be aware of these barriers and provide specific culturally sensitive information and care to this population.